Morphological Index as a Sensitive Marker of Drug Resistance in Leprosy: A Case Series - Namrata Chhabra; Tamil S. Kumar; Itu Singh; Satyaki Ganguly (Wolters Kluwer Medknow Publications, 2024)
Resistance to antileprosy drugs is one of the main contributors for the persistence of leprosy in the present era. In the absence of universal antimicrobial resistance (AMR) surveillance through the national program, the indications for resistance testing remain a important dilemma to clinicians. WHO recommendations mainly focus on clinical relapse, which could be picked up late with continued transmission and repeated leprosy reactions in the patient. We report here a series of eighteen leprosy cases who were tested for AMR in view of the positive morphological index after completion of multidrug therapy, chronic Erythema nodosum leprosum, and clinical relapse.